Hemiparasitic plants increase alpine plant richness and evenness but reduce arbuscular mycorrhizal fungal colonization in dominant plant species - McKibben, Michael; Henning, Jeremiah A. (PeerJ, 2018)
Hemiparasitic plants increase plant biodiversity by reducing the abundance of dominant plant species, allowing for the establishment of subordinate species. Hemiparasites reduce host resources by directly removing nutrients from hosts, competing for light and space, and may indirectly reduce host resources by disrupting plant associations with symbiotic root fungi, like arbuscular mycorrhizal fungi and dark-septate endophytes. Here, we explored how a generalist hemiparasite, Castilleja, influences plant richness, evenness, community composition, and mycorrhizal colonization patterns across a ∼1,000 m elevational gradient in the North American Rocky Mountains. We hypothesized that the presence of Castilleja would be associated with increased plant richness and evenness, shaping plant community composition, and would reduce mycorrhizal colonization within dominant plant taxa. However, the magnitude of the effects would be contingent upon climate contexts, that is, elevation. Overall, we found that the presence of Castilleja was associated with an 11% increase in plant richness and a 5% increase in plant evenness, regardless of elevation. However, we found that the presence of Castilleja influenced plant composition at only two of the five sites and at the remaining three of five sites, plot pairing was the only predictor that influenced composition. Additionally, we found that the presence of Castilleja reduced mycorrhizal fungal colonization within dominant plant species by ∼20%, regardless of elevation. Taken together, our results suggest that hemiparasites regulate plant diversity, evenness, and interactions with mycorrhizal fungi independent of abiotic and biotic contexts occurring at the site, although overall effect on community composition is likely driven by site-level factors.
Keywords: Castilleja; Arbuscular mycorrhizal fungi; Hemiparasites; Dark septate endophytes; Diversity; Elevational gradient